Flap surgery with bone graft and periodontal membrane in generalized chronic periodontitis patient - Ida Bagus Nyoman Dhedy Widyabawa; Anak Agung Istri Agung Feranasari (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Objectives: The aim of this case report is to present a flap surgical procedure with bone graft and periodontal membrane in generalized chronic periodontitis patients. Case Report: A 51-years-old male patient came to RSGM Saraswati bringing a referral from a colleague for dental and periodontal treatment. The patient came with complaints that the lower left gingiva often feels swollen, pain and mobility. Clinical examination revealed edema, sulcus exudate and positive percussion on tooth 36, the deepest pocket depth of 13 mm on the disto-buccal site. X-ray and blood laboratory examinations were carried out before surgery. Flap surgery is performed by internal bevel, sulcular and horizontal incisions with opening of the envelope flap, cleaning and smoothing of bone defects, application of collagen bone grafts and periodontal membranes, suturing with absorbable suture on the periodontal membrane and nylon on the gingiva flap. Conclusion: Flap surgery with bone graft and periodontal membrane is one of the options for reconstructive surgery to repair periodontal tissue in cases of generalized chronic periodontitis. The results showed the repair of periodontal tissue both soft tissue and alveolar bone of tooth 36.